Sistem Khilafah Pada Zaman Mamluk dan Analisis Terhadap Para Khalifah Dari 872H/1468M Sehingga 922H/1517M (Caliphate system during Mamluk Era and analysis of The Caliphs from 872H/1468AD To 922H/1517AD) - Wan Kamal Mujani, (Institut Kajian Rantau Asia Barat, 2012)
The aim of this article is to examine the continuity and survival ofthe „Abbasid Caliphate in Egypt during the Mamluk period after the„Abbasid Caliphate in Baghdad came to the end in 656AH/1258AD. It also seeks to discuss the position and power of the caliphs, especially during the period of 872H/1468M - 922H/1517M.For three and a half years the Islamic world was left without a caliph until it was revived by Sultan al-Zahir Baybars in 659H/1261M. Since then, the „Abbasid Caliphate continued in Egypt until the fall of the Mamluk kingdom in the hand of the Ottomans in 922H/1517M. The primary and secondary sources of this article find that the Abbasid caliphate during the reign of the Circassian Mamluk was also a continuation of the Abbasid caliphate which was re-established in the reign of the Turkish Mamluk. The Circassian sultans only continued the tradition of the caliphate which was restored by Turkish sultans without making any changes in the position and power of the caliphs. During the period from 872AH/1468AD till 922AH/1517AD, four individuals were installed as caliphs. They were descendents of al-Hakim bi Amr Allah. Accounts from primary sources also indicate that the caliphs in the Mamluk kingdom were weak and did not involved in any decision making process to legislate for government policy. Their life was controlled by the sultans, who bore the cost of their maintenance, thus making them in a difficult situation.